Spinal intradural arteriovenous fistula mimicking intramedullary tumor and associated with a giant intracranial aneurysm - Campos, Wuilker Knoner; da Silva, Benjamin Franklin; Damian Guasti, Jose Antônio (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2011)
Spinal intradural arteriovenous fistulas (AVFs) are a rare type of neurovascular malformation. Many a time hemodynamic disturbs associated to these entities can cause edema with subsequent myelopathy. On MRI study, this edema can mimic an intramedullary tumor. We report a rare case of spinal intradural AVFs mimicking an intramedullary tumor, which also were surprisingly associated with a giant intracranial aneurysm. We highlight in detail the MRI findings in intramedullary lesions, and also emphasize that these entities requires as careful differential diagnosis as supplementary investigation of the neuroaxis looking for other simultaneous neurovascular pathologies.
Keywords: Arteriovenous fistula; vascular malformations; spine; intracranial aneurysm; spinal cord/pathology